COMBINATION OF SOYBEAN MEAL AND Hibiscus tiliaceus LEAF IN THE GOAT DIET: EFFECT ON SOME PARAMETERS OF CARBOHYDRATE METABOLISM - Armayanti, A. K.; Nuswantara, L. K.; Achmadi, J. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The purpose of this study was to clarify effect of the combination of waru leaf (Hibiscus tiliaceus) sapponin with soybean meal protein in the goat diet on some parameters of carbohydrate metabolism. The study used 16 Ettawah cross bred male goats with body weight average of 16 kg and aged at 7 months. The dietary treatments were: T0 = total mixed ration (0.09% of Hibiscus tiliaceus leaf sapponin, 8.69 % of CP, 62.11% of TDN), T1 = T0 + 3% soybean meal protein, T2 = T0 + 6% soybean meal protein, and T3 = T0 + 9% soybean meal protein. The treatments were allotted in a completely randomized design, with 4 treatments and 4 replicates of each. The results showed that dietary treatments did not effect significantly (P>0.05) on intakes of dry matter, carbohydrate, energy, ruminal butirat and valerat concentrations. Crude protein intake, feed digestibility, ruminal acetate and propionate concentrations, ratio of non-glucogenic to glucogenic VFAs, and estimated methane production were increased (P<0.05) by dietary experiments. The protein supplementation in a Hibiscus tiliaceus leaf contained diet should be balanced with the energy level.